Comparative Evaluation of Harmless Acute Pancreatitis Score (HAPS) and Bedside Index of Severity in Acute Pancreatitis (BISAP) Scoring System in the Stratification of Prognosis in Acute Pancreatitis at Fang Hospital Chiang Mai - Chaosawat, Orawan (Journal of Phrae Public Health for Development - วารสารสาธารณสุขแพร่เพื่อการพัฒนา, 2025)
This retrospective observational study aimed to comparatively evaluate the sensitivity and specificity of the Harmless Acute Pancreatitis Score (HAPS) and Bedside Index for Severity in Acute Pancreatitis (BISAP) scoring systems in screening patients with acute pancreatitis at Fang Hospital. The sample consisted of 190 individuals diagnosed with acute pancreatitis at the Internal Medicine Department, Surgical Inpatient Department, and Surgical Critical Care Unit. Purposive sampling was used. Data analysis employed descriptive statistics and Cross-tabulation. The research findings revealed that, using the Harmless Acute Pancreatitis Score, there were 112 positive results, accounting for 58.95%. It demonstrated a sensitivity of 80.80% and a specificity of 68.30%. The negative predictive value was 82.80%, and the overall accuracy was 71.10%. Furthermore, using the Bedside Index for Severity in Acute Pancreatitis, with a score ≥ 3 predicting severe cases, it showed a sensitivity of 68.40% and a high specificity of 98.90%. The positive predictive value was 98.50%, and the overall accuracy was 83.70%. In conclusion, both BISAP and HAPS are useful tools for predicting the severity of acute pancreatitis. When compared, it was found that BISAP is particularly outstanding in terms of specificity, making it beneficial for confirming severe cases and identifying patients at high risk of mortality. It is recommended as the primary assessment tool for Fang Hospital. In contrast, HAPS demonstrates high sensitivity, which is advantageous for initial screening and does not require complex laboratory investigations. HAPS is particularly suitable for network community hospitals with limited specialized personnel and medical resources.